2014
DOI: 10.1002/ejoc.201301936
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of 3,4,6‐Trisubstituted 2,5‐Diketopiperazines by Using Dynamic Kinetic Resolution of α‐Bromo Tertiary Acetamides

Abstract: A new and efficient method for the asymmetric synthesis of 3,4,6‐trisubstituted 2,5‐diketopiperazines has been developed. The dynamic kinetic resolution of L‐amino‐acid‐derived α‐bromo tertiary amides in the nucleophilic substitution reaction with p‐anisidine and a subsequent deprotection‐cyclization process provides rapid access to diverse cis‐2,5‐diketopiperazines 5a–5o and proline‐containing trans‐2,5‐diketopiperazines 5p–5t in enantiomerically pure form in 45–67 % overall yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…(Experimental procedures for the preparation of 1, 12, 13, 14, 15, 32, 33 and 34 were described in previous publications. 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Experimental procedures for the preparation of 1, 12, 13, 14, 15, 32, 33 and 34 were described in previous publications. 14 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the syntheses of tetrasubstituted diketopiperazines require either multistep sequences or harsh conditions and they are inefficient for asymmetric synthesis. [7][8][9][10][11][12][13] As an extension of our previous work on the asymmetric preparation of 3,4,6-trisubstituted 2,5-diketopiperazines, 14 we herein report a mild and versatile synthetic method for the asymmetric synthesis of 1,3,4,6-tetrasubstituted 2,5-diketopiperazines via one-pot substitution-cyclization of α-bromo tertiary acetamides ( Figure 1). access to diverse highly functionalized diketopiperazines.…”
Section: Introductionmentioning
confidence: 99%
“…The inversion of dr for proline-based substrates compared to other amino acids was previously reported for the 2,5-diketopiperazine system. 11,12 Finally, the addition performed on seven-membered rings 5k and 5l led to the corresponding hemiaminals 6k and 6l in still good yields (62 and 55%, respectively) but with a lower dr (37 : 63), likely due to greater flexibility of the seven-membered ring. 13 As aforementioned for 6h and 6j, the X-ray diffraction analysis of 6l revealed that the major isomer was the C9-C2 cis-isomer.…”
mentioning
confidence: 98%